2008
DOI: 10.1021/es702137g
|View full text |Cite
|
Sign up to set email alerts
|

Emission Factor for Antimony in Brake Abrasion Dusts as One of the Major Atmospheric Antimony Sources

Abstract: Abrasion tests were conducted using a brake dynamometer to determine the antimony (Sb) emission factor originating from automobiles. Abrasion dusts from commercially available brake pads (nonasbestos organic type) were emitted into an enclosed chamber under various braking conditions in terms of initial driving speed and deceleration. Suspended dusts inside the chamber were collected on a quartz fiber filter and weighed. From the experimental data, dust emission could be regressed as a function of the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
99
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(112 citation statements)
references
References 20 publications
13
99
0
Order By: Relevance
“…For example, Ba, Cd, Cu, Fe, Mn, Sb, Sr, and Zn have been identified in previous studies as markers for traffic, vehicular emissions, or brake and tire wear (Olajire and Ayodele, 1997;Iijima et al, 2008;Harrison et al, 2011;Bukowiecki et al, 2010;Varrica et al, 2013). In the current study, traffic indicators (such as road networks and traffic volume) were significant predictors of Ba, Cd, Sb, and Sr in both summer and winter.…”
Section: Model Predictorssupporting
confidence: 70%
“…For example, Ba, Cd, Cu, Fe, Mn, Sb, Sr, and Zn have been identified in previous studies as markers for traffic, vehicular emissions, or brake and tire wear (Olajire and Ayodele, 1997;Iijima et al, 2008;Harrison et al, 2011;Bukowiecki et al, 2010;Varrica et al, 2013). In the current study, traffic indicators (such as road networks and traffic volume) were significant predictors of Ba, Cd, Sb, and Sr in both summer and winter.…”
Section: Model Predictorssupporting
confidence: 70%
“…Hjortenkrans et al [11] demonstrated that brake wear was one of the major sources of metal particulate emissions in Stockholm. Iijima et al [12] also concluded that airborne wear particles originating from brake wear contribute considerably to levels of PM 10 . Furthermore, Furusjö et al [13] identified brake wear as one of the major sources of PM 10 during urban driving.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have focused on wear and friction at the pad-rotor interface, few studies [12,15] have focused on airborne wear particles and none of these controls the cleanliness of the air surrounding the test specimens. Wahlström et al [16] have developed a disc brake assembly test stand that allows this to be done, ensuring that the wear particles measured and collected on the filters are airborne and that they originate from the padrotor contact.…”
Section: Introductionmentioning
confidence: 99%
“…The main uses of antimony are in vehicular brake devices and drugs (Iijima et al, 2008;Haldar et al, 2011), and both purposes are the main routes of human exposure to Sb. In recent years, it has become clear that the wear on vehicle braking systems generates Sb oxide accumulation in atmospheric particulate matter (von Uexküll et al, 2005), and it subsequently leads to human occupational exposure, leading to more than 15-fold of Sb exposure for these individuals than for non-exposed humans (Quiroz et al, 2013b(Quiroz et al, , 2009).…”
Section: Introductionmentioning
confidence: 99%